1999
DOI: 10.1046/j.1365-3156.1999.00479.x
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of natural killer cell activity in Chlamydia trachomatis infected individuals

Abstract: SummaryNatural killer (NK) cell activity is impaired in Chlamydia trachomatis-infected patients. The mechanisms behind the altered NK functions are not clear, but data concerning NK and antibody-dependent cellular cytotoxicity (ADCC) activity have been reported. To investigate whether this impairment is related to a defect at the target cell binding and/or the postbinding level, we evaluated highly purified NK cells obtained from 125 C. trachomatis-infected patients and compared them with 101 normal controls f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
9
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 51 publications
2
9
0
Order By: Relevance
“…This hypothesis is further supported by a prior study demonstrating that Ct EB-stimulated PBMCs had high levels of IFN-γ production by NK cells [13]. Interestingly, another study demonstrated that NK cell function (including IFN-γ production) was impaired in some Ct-infected humans [14]. Together, these findings suggest that NK cells may contribute to IFN-γ production in some, but not all, Ct-infected individuals and warrants further investigation.…”
Section: Discussionsupporting
confidence: 54%
“…This hypothesis is further supported by a prior study demonstrating that Ct EB-stimulated PBMCs had high levels of IFN-γ production by NK cells [13]. Interestingly, another study demonstrated that NK cell function (including IFN-γ production) was impaired in some Ct-infected humans [14]. Together, these findings suggest that NK cells may contribute to IFN-γ production in some, but not all, Ct-infected individuals and warrants further investigation.…”
Section: Discussionsupporting
confidence: 54%
“…Moreover, cytotoxic activity of these cells may be modulated during infections by both bacteria and viruses [19-21]. Also inflammation affects NK cell functions; our previous studies showed that high concentration of proinflammatory cytokines correlates with low NK cytotoxic activity [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…The important role of NK cells in host defense to infection has been demonstrated in several infection models including viral and intracellular bacterial infections (7)(8)(9). Limited studies have reported inconsistent findings on the role of NK cells in host immune response to chlamydial infections especially with different model systems (10)(11)(12)(13)(14)(15). In murine genital tract chlamydial infection, NK cells are found to be potent producers of IFN-g at the early stages of infection; NK cells are recruited into genital epithelium at early time points and may recognize/lyse infected cells (10).…”
mentioning
confidence: 99%
“…However, in the studies using lung infection models and genetically modified animals, it was found that the role of NK cells in host defense against chlamydial infection was negligible (12,14,15). Even in the studies showing a protective role of NK cells in host defense against chlamydial infection (10)(11)(12), the mechanism(s) remains largely unclear.…”
mentioning
confidence: 99%